2015
DOI: 10.1111/fcp.12141
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the antifibrillatory drug interactions between Amiodarone and Ibutilide in isolated, perfused Rabbit hearts

Abstract: In view of the reliability of the serial-shock method of measuring ventricular fibrillation threshold (VFT) in quantitatively assessing the antifibrillatory potency of many anti-arrhythmic drugs and the alarming reports of the proarrhythmic effects of several anti-arrhythmic agents, it was decided to use the above technique to study the possible interactions that may occur when anti-arrhythmic drugs from different classes are combined. Hearts isolated from New Zealand white rabbits of either sex weighing 1.5-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The researchers concluded that the cardiac lesions developed in rabbit hearts after single dose x-ray exposure resembled the lesions seen in humans [40]. Rabbits have since only been used by a few researchers to study RIHD [41,[114][115][116][117][118], although this species is commonly used to study cardiovascular disease from other causes [119][120][121][122][123][124][125]. There might be unique benefits to studying electrophysiological changes caused by radiation in rabbit models over rat models, as the rabbits' Ca2+ transport, action potential duration, and main ionic currents underlying repolarization are similar to humans [113,126,127].…”
Section: Animal Species Used In Preclinical Studies Of Rihdmentioning
confidence: 99%
“…The researchers concluded that the cardiac lesions developed in rabbit hearts after single dose x-ray exposure resembled the lesions seen in humans [40]. Rabbits have since only been used by a few researchers to study RIHD [41,[114][115][116][117][118], although this species is commonly used to study cardiovascular disease from other causes [119][120][121][122][123][124][125]. There might be unique benefits to studying electrophysiological changes caused by radiation in rabbit models over rat models, as the rabbits' Ca2+ transport, action potential duration, and main ionic currents underlying repolarization are similar to humans [113,126,127].…”
Section: Animal Species Used In Preclinical Studies Of Rihdmentioning
confidence: 99%